Innate immunity in ocular Chlamydia trachomatis infection: contribution of IL8 and CSF2 gene variants to risk of trachomatous scarring in Gambians - Joof Hassan; Rockett Kirk; Holland Martin; Luoni Gaia; Hull Jeremy; Natividad Angels; Burton Matthew; Mabey David; Kwiatkowski Dominic; Bailey Robin (BMC, 2009)
Abstract Background Trachoma, a chronic keratoconjunctivitis caused by Chlamydia trachomatis, is the world's commonest infectious cause of blindness. Blindness is due to progressive scarring of the conjunctiva (trachomatous scarring) leading to in-turning of eyelashes (trichiasis) and corneal opacification. We evaluated the contribution of genetic variation across the chemokine and cytokine clusters in chromosomes 4q and 5q31 respectively to risk of scarring trachoma and trichiasis in a large case-control association study in a Gambian population. Methods Linkage disequilibrium (LD) mapping was used to investigate risk effects across the 4q and 5q31 cytokine clusters in relation to the risk of scarring sequelae of ocular Ct infection. Disease association and epistatic effects were assessed in a population based study of 651 case-control pairs by conditional logistic regression (CLR) analyses. Results LD mapping suggested that genetic effects on risk within these regions mapped to the pro-inflammatory innate immune genes interleukin 8 (IL8) and granulocyte-macrophage colony stimulatory factor (CSF2) loci. The IL8-251 rare allele (IL8-251 TT) was associated with protection from scarring trachoma (OR = 0.29 p = 0.027). The intronic CSF2_27348 A allele in chromosome 5q31 was associated with dose dependent protection from trichiasis, with each copy of the allele reducing risk by 37% (p = 0.005). There was evidence of epistasis, with effects at IL8 and CSF2 loci interacting with those previously reported at the MMP9 locus, a gene acting downstream to IL8 and CSF2 in the inflammatory cascade. Conclusion innate immune response SNP-haplotypes are linked to ocular Ct sequelae. This work illustrates the first example of epistatic effects of two genes on trachoma.